Study of the most suitable new glass laser to incorporate ytterbium: alkali niobium tellurite, lead fluorborate or heavy metal oxide - Courrol, L. C.; Kassab, LRP; Morais, A. S.; Mendes, CMS; Gomes, L.; Wetter, N. U.; Vieira, N. D.; Cassanjes, F. C.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2003)
Diode-pumped Yb-doped glass lasers have received considerable attention for applications such as high-power beam production or femtosecond pulses generation. In this paper, we evaluate the laser potential of three different glass families doped with Yb3+ : alkali lead fluorborate (PbO-PbF2-B2O3), heavy metal oxide (Bi2O3-PbO-Ga2O3) and niobium tellurite (TeO2-Nb2O5-K2O-Li2O). Spectroscopic properties were studied for the samples and calculations of the minimum laser pump intensity (I-min), saturation fluence (U-sat) and the theoretical limit of peak power (P-max) are also presented. A comparison of laser properties of these three different glasses and their importance is shown and analyzed. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: laser; glasses; ytterbium; laser materials